THE ROLE OF NURUL UMMAHAT ISLAMIC BOARDING SCHOOL IN ACHIEVING RELIGIOUS MODERATION - Daimah, Daimah; Niam, Zainun Wafiqatun (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
In the era of globalization at this time, religious people are faced with religious plurality, social conflict and radicalism. Therefore, to realize the peace aspired to by the international world, it requires a person who still holds fast to the purity of religious teachings that are able to adapt to the culture of society and exclusively. And to realize such a person, we need an institution of religious education that teaches true religious values. This study uses a qualitative method and focuses on the role of the Nurul Ummahat Islamic boarding school in developing religious moderation so that the approach used is a sociological approach to religion. Research results show that the existence of the pesantren Nurul Ummahat as a religious education institution as well as an agent of peace has inspired the international world. In the midst of religious social conflicts, this pesantren is able to realize harmony in religious communities in the midst of domestic and international society. Through religious dialogues and cross-faith social practical activities, Nurul Ummahat was able to actualize the concept of Islam rahmatan lil 'alamin as the basis of Islamic boarding schools.